INTENSIFIKASI PELAJARAN MUATAN LOKAL UNTUK MENGURANGI KENDALA PENUNTASAN WAJIB BELAJAR - Mahlan Saman (Universitas Negeri Yogyakarta, 2003)
Abstract The aim of this research is to find ou tthe most appropriate step to anticipate the drop-out problem in State/Public Elementary School(SDN) and State /Public Junior High School (SLTPN), so that the fulfillment of compulsory education could be accomplished. The research is done by an action research, which is divided into three cycles. Every cycle consists of: planning, action, observation/ monitoring, and reflection to the observation. The writer had chosen 10 schools in South Kalimantan (5SDN and 5 SLTPN), which are relevant to the problem (from those schools there are 100 students from pre-prosperous family (pra sejahtera)). Data are collected by using questionnaires, observation, interviews, and are analyzed descripted in percentage. The results of this research are follows: (1) The first cycle: the action has succeeded to raise the students’ achievement from 6.59 to 6.96. (2) The second cycle: most of the students (60%) had understood “muatan local” (local content),(3) The third cycle: the students and the parents were able to run 81 kinds of small/ home industry (from muatan local), so that they could get benefit from their home industry and pay the school fee. Keywords: drop out, compulsory education, elementary education